Monitoring drug release and polymer erosion from therapeutically used biodegradable drug carriers by EPR and MRI in vitro and in vivo - Mäder, Karsten (Radiology and oncology (Ljubljana), 1998)
The in vivo performance of anticancer drugs is very often limited by their poor bioavailability, serious side effects and short half lives. During the last years, biodegradable drug carriers have been developed to overcome these problems. Despite the clinical use of these delivery systems, there is a rather poor understanding of the detailed mechanisms of drug realse and polymer erosion, particularly in vivo. The paper demonstrates how nonivasive magnetic resonance techniques ESR and MRI may contribute to increase our understanding of the in vivo fate of biodegradable drug delivery systems.
Keywords: Antineoplastic agents; Biodegradation; Drug carriers; Drug delivery systems; Electron spin resonance spectroscopy; Magnetic resonance imaging